Validation of the “My Headache Checker” that includes osmophobia in the diagnosis of migraine - Matsushita, Masahide (J Gen Fam Med, 2020)
BACKGROUND: Migraine is a common headache disorder, with a 1 year prevalence rate of 6.0 %. However, less than 10% of patients with migraine receive medication in hospital. “My Headache Checker,” a brief and self‐administered migraine screening tool, which includes osmophobia in addition to the ID‐Migraine™ three‐item subset, was developed. The objective of this study was to analyze the applicability of “My Headache Checker” in Japanese patients. METHODS: A total of 238 patients visiting the outpatient department were enrolled in the study. The patients’ chief complaint was not headache. “My Headache Checker” was administered to the patients. Subsequently, they were evaluated by a generalist for the diagnosis of headache. The clinical diagnosis of headache was determined based on the International Classification of Headache Disorders Ⅲ. RESULTS: Twenty (8.4%) patients satisfied the criteria for the diagnosis of migraine. Sensitivity, specificity, positive predictive value, and negative predictive value of “My Headache Checker” were 0.90, 0.83, 0.69, and 0.95, respectively. Sensitivity, specificity, positive predictive value, and negative predictive value of the ID‐Migraine™ were 0.90, 0.85, 0.72, and 0.95, respectively. CONCLUSION: The majority of migraine patients are missed in busy outpatient departments. Our results suggest that “My Headache Checker” is a useful tool in diagnosing unrecognized migraine patients. However, the addition of osmophobia did not contribute to improve the screening power of the ID‐Migraine™.